Smart Surveillance System Leveraging Machine Learning Techniques - C.M.Yasmeen; C.Yamini (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This project aims to develop an intelligent surveillance system capable of real-time video classification and activity detection to enhance public safety and threat prevention. The system categorizes video streams into three main classes: Normal, Violence, and Weaponized scenarios. To achieve this, a hybrid deep learning model is employed, integrating InceptionNet for spatial feature extraction and Gated Recurrent Units (GRU) for temporal sequence modeling. InceptionNet captures intricate spatial details from individual video frames, while GRU effectively learns the temporal patterns across sequences of frames. The system is trained on a comprehensive and diverse video dataset that simulates real-world conditions, ensuring robustness, high accuracy, and generalizability. Real-time monitoring and alert generation are core features of the proposed system, making it highly suitable for deployment in modern surveillance infrastructures. The project also investigates various optimization strategies to improve inference speed and efficiency, supporting practical implementation in real-time environments.